1992
DOI: 10.1111/j.1399-6576.1992.tb03509.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose oral omeprazole for reduction of gastric residual acidity in adults for outpatient surgery

Abstract: Omeprazole is a substituted benzimidazole that causes dose-dependent intracellular inhibition of gastric acid secretion in humans. This double-blind study examined the effect of omeprazole in decreasing gastric acidity and gastric residual volume in outpatient adults. Unpremedicated outpatients, ASA I-III, 18 years or older (n = 17), were randomly assigned to receive omeprazole 80 mg, or placebo by mouth the night before scheduled elective outpatient surgery. The patients were fasted for 8 h prior to surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The meta-analysis of 3 studies comparing residual gastric volumes after administration of proton pump inhibitors and placebo yielded a mean difference of 3.31 mL with a 95% CI of +2.34 to 4.68 (LOE- Moderate). [ 101 102 103 ] Mehta et al . conducted a study comparing three different proton pump inhibitors and found that the residual gastric volumes were comparable among them (LOE- Very Low).…”
Section: Adult Sectionmentioning
confidence: 99%
“…The meta-analysis of 3 studies comparing residual gastric volumes after administration of proton pump inhibitors and placebo yielded a mean difference of 3.31 mL with a 95% CI of +2.34 to 4.68 (LOE- Moderate). [ 101 102 103 ] Mehta et al . conducted a study comparing three different proton pump inhibitors and found that the residual gastric volumes were comparable among them (LOE- Very Low).…”
Section: Adult Sectionmentioning
confidence: 99%